Spatial Settlement Pattern of Settlements in Laweyan as Supportive Batik Production Activities - Rinaldi Mirsa; Sugiono Soetomo; Asnawi Asnawi (Indonesian Journal of Geography, 2016)
Laweyan, a traditional village, has existed before 1500 AD. As the trade center yarn (clothing material) of Pajang Kingdom, its presence meant after Kyai Ageng Anis (descendant of Brawijaya V) and grandson Raden Ngabehi Lor Ing Pasar who later became the first king of Mataram settled in Laweyan in 1546. Laweyan entrepreneurship in the communities ushered in the heyday of batik economic in century. Successfulness in the field of economy turned an impact on development in various fields, helped shape the pattern of space and environment. Spatial pattern and traditional settlements are usually much characterized by the mass of buildings that have appeared in the form of walls covered choke and surrounded by alley or narrow street, as seen in Laweyan with the existence of high ‘beteng’ which raises many narrow alleys and a Laweyan hallmark not only as a security but also one of the merchants attempt to maintain the privacy and obtain local authority in the community.